Acrokeratosis Paraneoplastica (Bazex Syndrome): A Case Report - Julia Holzgruber; Jacqueline Oberneder-Popper; Emmanuella Guenova; Wolfram Hötzenecker (Karger Publishers, 2022)
Acrokeratosis paraneoplastica Bazex is a rare paraneoplastic skin manifestation, typically causing acral psoriasiform lesions. Patients usually show erythematous hyperkeratosis with yellowish, adherent scales on the hands and feet or other acral locations such as ears or nose. We herein report a case of Bazex syndrome in a male patient, who was previously diagnosed with hepatocellular carcinoma. Our case report highlights this rare condition as early diagnosis may impact the patient's course of tumor disease and prognosis.